Comparing Fear of Childbirth and Labor Pain Intensity among Primiparous and Multiparous Women: A Cross-Sectional Study. - Nikpour, Maryam; Alijanpour, Masoumeh; Behmanesh, Fereshteh; Omrani, Atefeh; Yahyavi-Koochaksaraei, Fatemeh; Karimnezhad-Sorkhi, Fatemeh; Haghighi-Kenari, Tahereh; Hajian-Tilaki, Karimollah; Mohsenzadeh-Ledari, Farideh; Faramarzi, Mahbobeh (Journal of Midwifery & Reproductive Health, 2025)
Background & aim: Fear of Childbirth (FOC) can range from a general anxiety disorder to a specific, intense phobia related to pregnancy and childbirth. Labor pain, as an inevitable and multidimensional experience, is closely related to women's perception of childbirth and may interact with FOC. We conducted this study to compare the FOC and labor pain intensity in multiparous and primiparous women. Methods: This cross-sectional study was conducted on 432 pregnant women using convenience sampling in Babol, Iran, between January 2018 and June 2019. All pregnant women completed the demographic and fear of childbirth (FOC) questionnaires. Then, labor pain intensity was measured four times in labor and postpartum using a visual analog scale (VAS). Data were analyzed with student ttest, paired t-test and linear regression model using SPSS version 16. Results: FOC in primiparous women was significantly higher than in multiparous mothers (MD: 12.08, P<0.001). The multivariate linear regression showed that after adjusting the counfounding variables, in terms of intensity of pain in the active phase of labor (MD: 0.07; CI 95% -0.32, 0.47; P=0.71) and the phase of fetus expulsion (MD: 0.02; CI 95% -0.38, 0.44; P=0.89), there was no statistically significant difference between primiparous and multiparous women. However, multiparous women significantly experienced higher levels of pain compared with primiparous women during placental expulsion (MD: 0.52; CI 95% 0.01; P = 0.043). Conclusion: This study provides basic information for policy makers to pay more attention to reducing the fear and pain of childbirth in both primiparous and multiparous women.